Analisis Sootblower Terhadap Head Transfer Economizer Pada Boiler - Jainal Arifin; Firda Herlina (Jurnal Engine: Energi, Manufaktur, dan Material, 2022)
The Ministry of Energy and Mineral Resources (ESDM) said that the current national electricity consumption is still relatively small, namely one-quarter of the indicators of developed countries in the world. With a figure of 956 Kilowatt-hour (KWh) per capita, Indonesia's electricity consumption has only reached 23.9% of the electricity consumption of developed countries of 4000 KWh per capita. Based on field observation data, the temperature in the economizer pipe ranges from 280 0C to 330 0C even though it should be between 350 0C to 470 0C (Manual Book PT. Wijaya Triutama) is based on operational standards for a maximum load of 4 MW. A decrease in the temperature in the economizer pipe which is already below the limit will certainly cause a reduction in the electrical power generated and then fuel consumption will increase from 5 tons of wood waste per hour to 7 tons of wood waste per hour. Based on data analysis and discussion, conclusions can be drawn regarding the economizer analysis on boilers that work below the normal limit of gas temperature of 330.9 0C which should be normal temperature of 470.6 0C then water temperature of 152.3 0C which should be 234.8 0C due to several factors including is the contamination in the economizer pipe which causes the temperature to drop, then the efficiency value in the economizer before the research is 58.0% and after repairs and cleaning of the economizer pipe is 70.2% the value of the temperature increase is very influential on the boiler that produces steam pressure Very large.